1985
DOI: 10.1007/bf01252027
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine and a ?-agonists induce hyperthermia in rats at high ambient temperature

Abstract: The effects of the alpha-agonist clonidine and the beta-agonist clenbuterol on body temperature of rats kept at high ambient temperature (28 degrees C) were studied. Both drugs induced a dose-dependent significant increase in temperature. The clonidine-induced hyperthermia was blocked by various alpha 2-antagonists, yohimbine, rauwolscine and RX 781094 and the alpha 1-antagonists, prazosin and corynanthine but not by 1-propranolol, spiperone, metergoline. The hyperthermic effect of clonidine was potentiated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…This strongly implies that the OC2-adrenoceptors in question are situated in the central nervous system. A recent report has also suggested that the hyperthermia elicited by clonidine in rats maintained at a high ambient temperature is mediated via central postsynaptic a2-adrenoceptors (Mogilnicka et al, 1985). The results of the present study provide no clue to the mechanisms beyond the level of the central x2-adrenoceptor ultimately responsible for producing an increase in the body temperature of reserpinized mice after the administration of a2-agonists.…”
Section: Effects Ofsingle Doses Ofidazoxan Indoramin and Propranololcontrasting
confidence: 49%
“…This strongly implies that the OC2-adrenoceptors in question are situated in the central nervous system. A recent report has also suggested that the hyperthermia elicited by clonidine in rats maintained at a high ambient temperature is mediated via central postsynaptic a2-adrenoceptors (Mogilnicka et al, 1985). The results of the present study provide no clue to the mechanisms beyond the level of the central x2-adrenoceptor ultimately responsible for producing an increase in the body temperature of reserpinized mice after the administration of a2-agonists.…”
Section: Effects Ofsingle Doses Ofidazoxan Indoramin and Propranololcontrasting
confidence: 49%
“…As we found in our previous paper (Mogilnicka et al, 1985), both a2-and 0~l-adrenoceptors participate in CLON-induced hyperthermia. Since both types of adrenoceptors are involved in the hyperthermic response to CLON, this test does not seem to be specific.…”
Section: Discussionmentioning
confidence: 72%
“…It seems that the observed alterations result from changes in a2-adrenoceptors postsynaptic since, as was found in previous papers, the a2-adrenoceptors that mediate CLON-induced sedation or hyperthermia are located postsynaptically (Mogilnicka et al, 1985;Spyraki and Fibiger, 1982).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These studies required separate surgical implantations using different groups of animals to record changes in TST and CBT measurements. The compounds, clonidine (alpha 2 adrenergic agonist) (Mogilnicka et al, 1985), MDL-100907 (MDL, 5-HT 2a antagonist) (Sipe et al, 2004) and 17␣-ethinyl estradiol (EE, estrogen receptor agonist) (Sipe et al, 2004) have been previously reported to affect temperature in rats but the temporal relationship between TST and CBT has not been reported. Therefore, these test compounds were used to compare the sensitivity and reproducibility of the two types of temperature probes.…”
Section: Introductionmentioning
confidence: 98%